2019
DOI: 10.1007/s11071-019-05324-8
|View full text |Cite
|
Sign up to set email alerts
|

Toppling dynamics of a mass-varying domino system

Abstract: The version presented here may differ from the published version. If citing, you are advised to consult the published version for pagination, volume/issue and date of publication Noname manuscript No.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 31 publications
0
11
0
Order By: Relevance
“…All previous investigation did not take into account the dominoes width [3][4][5][6][7][8][9][10][11][12][13][14]. The reason is perhaps that the dominoes width has little influence on the velocity of dominoes toppling motion, the problem is how to justify this statement.…”
Section: Influence Of Dominoes Width and Mass On The Toppling Velocitymentioning
confidence: 99%
See 2 more Smart Citations
“…All previous investigation did not take into account the dominoes width [3][4][5][6][7][8][9][10][11][12][13][14]. The reason is perhaps that the dominoes width has little influence on the velocity of dominoes toppling motion, the problem is how to justify this statement.…”
Section: Influence Of Dominoes Width and Mass On The Toppling Velocitymentioning
confidence: 99%
“…The domino effect is not only an interesting game but also an important physical phenomena, and often be used to describes some social catastrophe, such as the cascading consequences of research misconduct [1]. The mechanics of domino falling has been studied extensively by number of leading scholars [2][3][4][5][6][7][8][9][10][11][12][13][14]. In 1983, McLachlan et al [4] found a scaling law for the velocity v in the limiting case of dominoes with zero thickness spaced in a straight line.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Shi et al [13] developed a precise numerical model with consideration of multipoint impacts between dominoes. Shi et al [14] studies the toppling dynamics of a mass-varying domino system for which the mass of the domino changes at an exponential rate of its sequence number.…”
Section: Introductionmentioning
confidence: 99%
“…The domino effect is not only an interesting game but also an important physical phenomena, and often be used to describes some social catastrophe, such as the cascading consequences of research misconduct [1]. The mechanics of domino falling has been studied extensively by number of leading scholars [2][3][4][5][6][7][8][9][10][11][12][13][14]. In 1983, McLachlan et al [4] found a scaling law for the speed v in the limiting case of dominoes with zero thickness spaced in a straight line.…”
Section: Introductionmentioning
confidence: 99%